Quadrature frequency generation for wideband wireless applications - Elbadry, Mohammad; Harjani, Ramesh (Analog Circuits and Signal Processing, 2015)
This book describes design techniques for wideband quadrature LO generation for software defined radio transceivers, with frequencies spanning 4GHz to around 80GHz. The authors discuss several techniques that can be used to reduce the cost and/or power consumption of one of the key components of the RF front-end, the quadrature local oscillator.  The discussion includes simple and useful insights into quadrature VCOs, along with numerous examples of practical techniques. ·         Provides a thorough survey of  quadrature LO generation; ·         Offers an intuitive explanation of the different quadrature VCO architectures, and categorization of these architectures based on the intuitive explanations; ·         Describes a new technique for simultaneous quadrature LO generation for channelized receivers; ·         Includes simple and detailed explanation of two new quadrature VCO techniques that improve phase-noise performance of QVCOs, while providing a large tuning range.